2000
DOI: 10.24266/0738-2898-18.3.142
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Best Management Practices in Container Production Nurseries

Abstract: Twenty-four nurseries producing container-grown plants were surveyed along the coastal zone of south Alabama to determine Best Management Practices (BMPs) implemented since 1988. All nurseries utilized multiple BMPs. Seventy-five percent of all nurseries surveyed have the capability to capture runoff water; however, larger nurseries (medium 4.5–16.6 ha (11–40 A); large 16.6+ ha (40+A)) were more likely to capture runoff than smaller nurseries 0.4–4.1 ha (1–10 A). Since 1988, 78% of all collection ponds have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 3 publications
0
12
0
4
Order By: Relevance
“…Facing this situation, industry must learn how to effectively manage water use in the nursery. Several states are encouraging nurseries to implement BMPs and surveys have shown that nurseries can be proactive in addressing environmental issues related to production of container-grown crops (Fain et al, 2000;Garber et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Facing this situation, industry must learn how to effectively manage water use in the nursery. Several states are encouraging nurseries to implement BMPs and surveys have shown that nurseries can be proactive in addressing environmental issues related to production of container-grown crops (Fain et al, 2000;Garber et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the greenhouse and fl oriculture industries, there is little information on nutrient recycling in container nursery culture (Gori and Lubello, 2000). Some container nurseries have used retention ponds to capture leachates and recycle them through the irrigation systems (Fain et al, 2000). However, without HORTSCIENCE 39(1): 60-64.…”
Section: Methodsmentioning
confidence: 99%
“…growing recognition that intensive plant production operations are having a significant impact on the local environment. Starting in the early 1980s, a number of nursery researchers recognized that many best management practices could be implemented that would improve resource use efficiency, increase productivity, and reduce the overall environmental impacts of those practices (Wright and Niemiera 1987;Yeager et al 1997;Fain et al 2000;Bilderback 2001;Yeager et al 2007). This culminated in the development of the first set of Best Management Practice (BMP) guidelines for the nursery industry (Yeager et al 1997), which was significantly reviewed and updated by Yeager et al (2007).…”
Section: Scope Of the Reviewmentioning
confidence: 99%